2020
DOI: 10.1080/19336918.2019.1710015
|View full text |Cite
|
Sign up to set email alerts
|

Effect arylamine N-acetyltransferase 1 on morphology, adhesion, migration, and invasion of MDA-MB-231 cells: role of matrix metalloproteinases and integrin αV

Abstract: Reducted arylamine N-acetyltransferase (NAT1) in breast cancers is associated with poor patient survival. NAT1 has also been associated with changes in cancer cell survival and invasion both in vitro and in vivo. Here, we report the effects of NAT1 in cancer cell invasion by addressing its role in adherence, migration, and invasion in vitro. The NAT1 gene was deleted in MDA-MB-231, HT-29 and HeLa cells using CRISPR/Cas9 gene editing. Loss of NAT1 increased adherence to collagen in all three cell-lines but migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Thus, the increased MMP9 expression in NAT1 KO cells is not in agreement with the preceding reports of a decrease in invasion following NAT1 deletion or inhibition. Moreover, in a follow‐up study, the authors reported that deletion of NAT1 in MDA‐MB‐231, HT‐29, and HeLa cells did not affect cell migration and rather increased adherence to collagen in all three cell lines 26 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the increased MMP9 expression in NAT1 KO cells is not in agreement with the preceding reports of a decrease in invasion following NAT1 deletion or inhibition. Moreover, in a follow‐up study, the authors reported that deletion of NAT1 in MDA‐MB‐231, HT‐29, and HeLa cells did not affect cell migration and rather increased adherence to collagen in all three cell lines 26 …”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in a follow-up study, the authors reported that deletion of NAT1 in MDA-MB-231, HT-29, and HeLa cells did not affect cell migration and rather increased adherence to collagen in all three cell lines. 26 With MDA-MB-231 cells which showed robust cell growth in vivo, metastasis to the lung was readily observed in all animals. The metastatic focus formed by NAT1 KO cells was significantly smaller F I G U R E 6 Formation of xenograft by parental versus NAT1 KO MDA-MB-231 cells following different engraftment protocols.…”
Section: Cell Proliferation and Death (Apoptosis) In Primary Tumorsmentioning
confidence: 96%
“…In this study we identified additional supportive evidence of an association between NAT1 and cell adhesion molecules. Many have noted that overexpression NAT1, specifically in breast cancer, is associated with increased metastasis ( Smid et al, 2006 ; Savci-Heijink et al, 2016 ; Zhao et al, 2020 ) and growth ( Adam et al, 2003 ) and conversely knockdown or deletion of NAT1 leads to increased adherence to collagen ( Li et al, 2020 ) and decreased invasion ( Tiang et al, 2010 , 2015 ; Li et al, 2020 ), E-cadherin up-regulation and cell-cell contact growth inhibition ( Tiang et al, 2011 ), and reduced anchorage independent growth ( Stepp et al, 2018 ; Stepp et al, 2019 ). Here we have shown the expression of many members of the cadherin family of proteins are associated with NAT1 N -acetylation activity.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a relationship between NAT1 and the conjugation of carnitine with fatty acyl-CoA moieties ( Carlisle et al, 2020 ). Others have shown deletion of the NAT1 gene in MDA-MB-231, HT-29 and HeLa cancer cell lines leads to increased collagen adherence, decreased invasion, and morphological changes but no changes to migration ability in all three cell-lines ( Li et al, 2020 ). Despite numerous studies investigating NAT1 in breast cancer, the exact effect of increased NAT1 expression in breast cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NAT1 is frequently upregulated in estrogen receptor-positive breast cancers as well as triple-negative breast cancers [ [7] , [8] , [9] , [10] ]. This led us and others to investigate the role of NAT1 in cancer cell growth, morphology and metastasis in recent years [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%